2010
DOI: 10.1001/archgenpsychiatry.2010.1
|View full text |Cite
|
Sign up to set email alerts
|

Severe Mental Disorders in Offspring With 2 Psychiatrically Ill Parents

Abstract: Derived risks may be informative for counseling. Patterns of transmission may support evolving assumptions about genetic overlap for traditional categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
159
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(176 citation statements)
references
References 31 publications
11
159
1
5
Order By: Relevance
“…Although parental BD is a robust indicator of concordant offspring disorder (Duffy et al, 2010;Gottesman et al, 2010), we did not focus on individual parental diagnoses as risk elevation is not confined to concordant disorders (Dean et al, 2010). Therefore in subsequent analyses parental psychopathology was collapsed into a single variable and was considered absent or present regardless of the individual parental diagnoses.…”
Section: Baseline Assessments Of Trails Participants At Age 11 Yearsmentioning
confidence: 99%
“…Although parental BD is a robust indicator of concordant offspring disorder (Duffy et al, 2010;Gottesman et al, 2010), we did not focus on individual parental diagnoses as risk elevation is not confined to concordant disorders (Dean et al, 2010). Therefore in subsequent analyses parental psychopathology was collapsed into a single variable and was considered absent or present regardless of the individual parental diagnoses.…”
Section: Baseline Assessments Of Trails Participants At Age 11 Yearsmentioning
confidence: 99%
“…This confirms results from population registry and genetic studies that report overlap of familial and genetic risk to various mental disorders. 2,3,25 The results of the meta-analysis also suggest that familial transmission can be heterotypic (different from parent diagnosis), yet diagnosis specific: the risk of anxiety disorders was elevated in offspring of parents with bipolar disorder or depression, but not in offspring of parents with schizophrenia. The heterotypic familial transmission supports recent findings from molecular genetic analyses suggesting shared genetic factors underlying schizophrenia, bipolar disorder and major depression.…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3][4] Individuals with SMI want to know the probability that their offspring will develop SMI. Accurate quantification of risk is an important element in communication with patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, large scale epidemiological studies from Scandinavia, which have linked national population registers with mental health service registers, have provided further information on the patterns of familial risks. One such study found the risk of schizophrenia in the offspring of couples who had both been admitted to a psychiatric facility with a diagnosis of schizophrenia was 27.3% (increasing to 39.2% when schizophrenia-related disorders were included) [4]. This was compared with a risk of schizophrenia of 7% in the offspring of couples with only one parent ever admitted for schizophrenia and 0.9% in the offspring of couples where neither had ever been admitted [4].…”
Section: Family Studiesmentioning
confidence: 99%